Implementation Of Balanced Scorecard Based Educational Management Evaluation Model - Dodi Setiawan Riatmaja; Jeprianto Jeprianto; Andi Nuzul Hikmah Buana (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
Effective education management requires a comprehensive and data-driven evaluation system to ensure continuous quality improvement. Balanced Scorecard (BSC) is a strategic evaluation model that allows educational institutions to measure performance from four main perspectives, namely financial, customer, internal processes, and growth and learning. By implementing BSC, educational management can identify strengths and weaknesses in resource management, learning effectiveness, stakeholder satisfaction, and teacher development. This study examines the implementation of BSC in educational management evaluation, showing that this approach can improve transparency, operational efficiency, and the relevance of the education system to the needs of the times. Despite challenges such as resistance to change and limited resources, the implementation of BSC has been proven to provide strategic benefits in improving the quality of education. With BSC-based evaluation, educational institutions can develop policies that are more adaptive, innovative, and oriented towards improving quality as a whole.